REAKSI PASAR TERHADAP PENGUMUMAN DIVIDEN TUNAI (STUDI EMPIRIS PADA PERUSAHAAN-PERUSAHAAN YANG TERDAFTAR DI KOMPAS 100) - B31112033, NURQOMARA (Jurnal Manajemen Update, 2016)
This research aims to determine the market's reaction to the cash dividends announcement by companies listed in Compass 100. The market reaction is measured by the average abnormal return and average trading volume activity (TVA). This research used event study method to the window period for 21 days. The sample was selected with purposive sampling method, where obtained 62 companies. This research use done sample t-test and independent sample t-testas tools for statistical test. The results showed that the market respond to the cash dividends announcement with a positive and negative response. When the company announced a cash dividends, it will affect the changes of stock price. But there was no difference in the volume of stock trading before and after the cash dividends announcement. Overall, cash dividends announcement contains information that could affect stock price and is useful as a basis for investors in making investment decisions. Keywords : Dividends Announcement, Abnormal Return, Stock Trading Volume, Event Study.